REELS study of a LiNi1/3Mn1/3Co1/3O2 positive electrode. (27th July 2016) - Taguchi, N.; Kitta, M.; Sakaebe, H.; Akita, T.
Abstract : Li K ‐edge analysis obtained by scanning reflection energy loss spectroscopy (REELS) has been used to investigate the positive electrode of a Li‐ion battery. Using spectral imaging data, Li mapping of a LiNi1/3 Mn1/3 Co1/3 O2 electrode has been constructed. Inhomogeneous Li distributions are observed in LiNi1/3 Mn1/3 Co1/3 O2 particles after cyclic electrode charging and discharging. The REELS results agree well with those obtained by scanning transmission electron microscopy‐electron energy loss spectroscopy (STEM‐EELS). Copyright © 2016 John Wiley & Sons, Ltd.